The biomechanical effect of arm mass on long jump performance: A case study of a paralympic upper limb amputee. (June 2014) - Pradon, Didier; Mazure-Bonnefoy, Alice; Rabita, Giuseppe; Hutin, Emilie; Zory, Raphael; Slawinski, Jean
Background: The role of arm motion during the long jump has been well studied. The aim of this study was to quantify the effect of forearm mass on impulse and the kinematics of the flight phase in an upper limb amputee. Case description and methods: A world-record paralympic long jumper carried out jumps in three conditions: wearing his usual forearm prosthesis and with 0.3 and 0.4 kg added mass. A motion capture system including force plates was used to record the jump. Findings and outcome: At take-off, the addition of 0.4 kg to the prosthesis decreased the vertical velocity of the centre of mass but increased horizontal velocity. These modifications were associated with an increase in landing distance and an improvement of the synchronization between arms. Conclusion: Increasing forearm mass appears to improve long jump performance. Further studies need to evaluate the optimal prosthetic mass for both training and competition. Clinical relevance: This biomechanical analysis of the long jump highlighted the effects of changing prosthesis mass on performance. This methodological approach may be useful in the context of sport and performance research.